Answer:
![f^{-1}(8)=\frac{3}{2}](https://tex.z-dn.net/?f=f%5E%7B-1%7D%288%29%3D%5Cfrac%7B3%7D%7B2%7D)
Step-by-step explanation:
Given f(x)=![2x+5](https://tex.z-dn.net/?f=2x%2B5)
We have to find ![f^{-1}(8)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%288%29)
In order to find
we have to make x as the subject of the formula
Let us assume f(x)=y
⇒![2x+5=y](https://tex.z-dn.net/?f=2x%2B5%3Dy)
Subtracting both sides by 5
![2x+5-5=y-5](https://tex.z-dn.net/?f=2x%2B5-5%3Dy-5)
![2x=y-5](https://tex.z-dn.net/?f=2x%3Dy-5)
Dividing both sides by 2
![\frac{2x}{2}=\frac{y-5}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%7D%7B2%7D%3D%5Cfrac%7By-5%7D%7B2%7D)
⇒![x=\frac{y-5}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7By-5%7D%7B2%7D)
Now substituting y with x
we have ![f^{-1}(x)=\frac{x-5}{2}](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3D%5Cfrac%7Bx-5%7D%7B2%7D)
Now ![f^{-1}(8)=\frac{8-5}{2}](https://tex.z-dn.net/?f=f%5E%7B-1%7D%288%29%3D%5Cfrac%7B8-5%7D%7B2%7D)
=![\frac{3}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B2%7D)
So option (ii) is correct
Answer:
100/9
Step-by-step explanation:
(7*5*2/7*3)² * (5^0/2^-3)³ * 2^-9
Solution:
We know that any number with power 0 = 1
(7*5*2/7*3)² * (1/2^-3)³ * 2^-9
Now cancel out 2 by 2
= (7*5*2/7*3)² * (1/1^-3)³ * 1^-9
=(70/21)² * (1)³/(1^-3)³ * 1^-9
=(10/3)^2 * 1/1^-1 * 1/1^9
=100/9 *1 *1
=100/9....
Answer:
5045
Step-by-step explanation:
multiply